THE UTILIZATION OF INSTAGRAM AS A PROMOTIONAL MEDIA IN MARKETING COMMUNICATION STRATEGY IN THE CULINARY INDUSTRY DURING THE COVID-19 PANDEMIC (@kulinertegal Instagram Account Case Study) - Nadia Safina Faradis; Yanuar Luqman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The @KulinerTegal account promotes the culinary industry with a unique strategy, apart from taking high-resolution food pictures, the account also does story telling through the latest Instagram reels feature by clearly explaining the food products they promote. Through this strategy, the @KulinerTegal account is expected to attract consumer buying interest. The purpose of this study is to find out what strategies make Instagram an effective and representative promotional media during the Covid-19 pandemic. This study uses a qualitative descriptive approach with a case study type to describe and understand the existing phenomena. This type of approach was chosen to study the case intensively, in-depth, in detail and comprehensively. The case study approach is directed at collecting data, taking meaning and gaining understanding from the case. The researcher concludes that Instagram is an effective and representative promotional media during the Covid-19 pandemic because Instagram itself has a lot of increasing popularity which is marked by the number of users that has increased significantly in recent years. Besides that, Instagram also offers its users where the user interface that is displayed makes it easier for users to connect so that it is easier to use, it can display features that can optimize content distribution and are perceived well by users.